Contribution of Blood Orange-Based Beverages to Bioactive Compounds Intake - Licciardello, Fabio; Arena, Elena; Rizzo, Valeria; Fallico, Biagio (Frontiers in Chemistry, 2018)
The study aimed at screening the levels of ascorbic acid, hydroxycinnamic acids (HCAs) and total anthocyanins in commercial beverages containing blood orange juice (BOJ), estimating the contribution of these products to the intake of health-promoting compounds and at discussing the actual value of the products on a price/bioactive level basis. Results demonstrate that the reference to BOJ in many beverages is misleading, as inferred from the very low bioactive levels observed. These beverages, in label should refer as “water-based” instead of “fruit-based beverage”. Accordingly, the intake of bioactives from BOJ-based beverages, with the exception of ascorbic acid used in the most cases as preservative, is often very low. The intake of bioactive components from blood orange consumption is much higher compared to the consumption of BOJ-based beverages, hence the consumption of blood oranges and 100% BOJs should be preferred in order to guarantee the intake of a rich pool of bioactive compounds. Finally, the market value of BOJ-based beverages is not correlated with their real nutritional value: the relative unitary cost of the three classes of bioactive compounds considered increased in the order: fresh blood oranges < 100% BOJ < BOJ-based beverages. Hence, the consumption of fresh blood oranges represents the cheapest way to ensure the intake of health-promoting bioactive compounds such as anthocyanins and HCAs.